Mechanism of interventional effect and targets of Zhuyu pill in regulating and suppressing colitis and cholestasis - Yu, Han; Zhang, Fenghua; Wen, Yueqiang; Zheng, Zhili; Chen, Gaoyang; Pan, Yingying; Wu, Peijie; Ye, Qiaobo; Han, Jun; Chen, Xiaofeng; Liu, Chao; Shen, Tao (Frontiers in Pharmacology, 2022)
Zhuyu pill (ZYP) is a traditional Chinese medicine prescription composed of two drugs, Coptis chinensis Franch. and Tetradium ruticarpum (A. Jussieu) T. G. Hartley, and is commonly used in the clinical treatment of diseases of the digestive system. However, the mechanism underlying the effect of ZYP on colitis remains unclear. In this study, a colitis rat model was induced with 2,4,6-trinitro-benzenesulfonic acid (TNBS, 100 mg/kg) and treated with ZYP (low dose: 0.6 g/kg, high dose: 1.2 g/kg). Disease activity index, colonic weight index, and weight change ratio were used to evaluate the model and efficacy. LC-MS and 16S rRNA gene sequencing were used to measure differences in fecal metabolism and microorganism population among the control, model, low-dose ZYP, and high-dose ZYP groups. To elucidate the mechanism of interventional effect of ZYP, Spearman correlation analysis was used to analyze the correlation between fecal metabolism and fecal microbial number. High-dose and low-dose ZYP both exhibited significant interventional effects on colitis rat models, and high-dose ZYP produced a better interventional effect compared with low-dose ZYP. Based on a metabolomics test of fecal samples, significantly altered metabolites in the model and high-dose ZYP treatment groups were identified. In total, 492 metabolites were differentially expressed. Additionally, sequencing of the 16S rRNA gene in fecal samples revealed that the high-dose ZYP could improve TNBS-induced fecal microbiota dysbiosis. Ultimately, changes in tryptophan metabolism and Firmicutes and Gammaproteobacteria populations were detected after ZYP treatment in both colitis and cholestasis. Therefore, we conclude that tryptophan metabolism and Firmicutes and Gammaproteobacteria populations are the core targets of the anti-inflammatory effect of ZYP. These findings provide a scientific basis for further investigation of the anti-inflammatory mechanism of ZYP in the future.